Diagnostic Significance of Plasma Levels of Novel Adipokines in Patients With Symptomatic Intra- and Extracranial Atherosclerotic Stenosis - Yu, Fang; Zhou, Xiaoqing; Li, Zhibin; Feng, Xianjing; Liao, Di; Liu, Zeyu; Huang, Qin; Li, Xi; Yang, Qidong; Xiao, Bo; Xia, Jian (Frontiers in Neurology, 2019)
Background: Adipokines have been proven to be associated with atherosclerotic diseases such as ischemic stroke and coronary heart disease. The role of novel adipokines in the development of symptomatic intracranial atherosclerotic stenosis (sICAS) and extracranial atherosclerotic stenosis (sECAS) has not yet been investigated. This study aimed to evaluate the plasma levels of novel adipokines in patients with sICAS and sECAS and their associations with the prognosis of sICAS groups. Methods: A total of 134 patients with acute ischemic stroke attribute to large-artery atherosclerosis (LAA) and 66 age- and sex-matched controls without atherosclerotic stenosis (NCAS) were included in this study. The LAA group was further sub-classified as sICAS (n = 102) and sECAS (n = 32) according to the location of atherosclerosis. Demographics, clinical parameters, angiographical features and plasma levels of novel adipokines (apelin, visfatin, omentin, RBP-4) were assayed and compared among groups. Results: LAA patients had significantly lower levels of omentin [39.92 (30.74–52.61) ng/ml vs. 54.42 (34.73–79.91) ng/ml, P < 0.001] and visfatin [11.32 (7.62–16.44) ng/ml vs. 13.01 (9.46–27.54) ng/ml, P < 0.001] than those in the NCAS group. Multiple logistic regression analysis identified that the lowest tertile of omentin was independently associated with LAA (OR, 3.423; 95% CI, 1.267–9.244, when referenced to the third tertile). Levels of omentin, visfatin and RBP-4 showed no significant difference between sICAS and sECAS groups. However, median concentrations of apelin were lower in sECAS [84.94 (46.88–130.41) ng/mL) than in sICAS [118.64 (93.22–145.08) ng/mL, P = 0.002] and NCAS [114.38 (80.56–162.93) ng/mL, P = 0.004]. Logistic regression analysis showed that the lowermost tertile of apelin was independently associated with sECAS (OR, 5.121; 95% CI, 1.597–16.426) when adjusted for risk factors. As for sICAS patients, spearman coefficient analysis showed no significant correlation between these four adipokines and the severity of sICAS or the number of vessels with intracranial stenoses. Patients with severe stroke had lower levels of apelin (P = 0.005), while the other three adipokines showed no such difference. During follow up, no difference was found between these four novel adipokines and short- and long-term outcome of sICAS. Conclusions: Lower levels of omentin are independent biomarkers of LAA while low apelin plasma levels seem to be risk factors of sECAS.